Biomass-derived nitrogen-doped carbon quantum dots: highly selective fluorescent probe for detecting Fe3+ ions and tetracyclines - Qi, Houjuan; Teng, Min; Liu, Miao; Liu, Shouxin; Li, Jian; Yu, Haipeng; Teng, Chunbo; Huang, Zhanhua; Liu, Hu; Shao, Qian; Umar, Ahmad; Ding, Tao; et al. (Journal of colloid and interface science, 2019)
[Display omitted] Nitrogen-doped carbon quantum dots (N-CQDs) were successfully synthesized using rice residue and glycine as carbon and nitrogen sources by one-step hydrothermal method. High quantum yield (23.48%) originated from the effective combination of nitrogen with various functional groups (CO, NH, CN, COOH and COC). The N-CQDs showed a fluorescence with the wavelength varied from 420 to 500 nm and the maximum emission wavelength being at 440 nm. N-CQDs have been importantly applied as probe to detect Fe3+ and tetracycline (TCs) antibiotics with remarkable performance. Using the linear relationship between fluorescence intensity and Fe3+ concentration, the N-CQDs could be employed as a simple, efficient sensor for ultrasensitive Fe3+ detection ranging from 3.32 to 32.26 µM, with a limit of detection (LOD) of 0.7462 µM. The N-CQDs showed the applicability to detect TCs. The detection limits of tetracycline, terramycin and chlortetracycline were 0.2367, 0.3739 and 0.2791 µM, respectively. The results of TC by fluorescence method in real water samples were in good agreement with standard Ultraviolet–visible (UV–vis) method. The N-CQDs have various potential applications including sensitive and selective detection of Fe3+ and TCs, and cellular imaging with low cytotoxicity, good biocompatibility and high permeability.